Application of polyetheretherketone (PEEK) posts: evaluation of fracture resistance and stress distribution in the root: in vitro and finite element analyses - Michele Oliveira LIMA; Marcela Alvarez FERRETTI; Ricardo Armini CALDAS; Valentim Adelino Ricardo BARÃO; Fabiana Mantovani Gomes FRANÇA; Débora Alves Nunes Leite LIMA; Luís Roberto MARTINS; Flávio Henrique Baggio AGUIAR (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract To evaluate the feasibility of using a milled polyetheretherketone (PEEK) post and core in endodontically treated teeth with or without a ferrule. Sixty bovine tooth roots were endodontically treated followed by cementation of intraradicular retainers (IR), according to each experimental group: a) non-ferrule glass fiber post (f0FP); b) 2-mm-ferrule glass fiber post (f2FP); c) non-ferrule resized glass fiber post (f0PR); d) 2-mm-ferrule resized glass fiber post (f2PR); e) non-ferrule PEEK post and core (f0PPC); and f) 2-mm-ferrule PEEK post and core (f2PPC). Metal crowns were made and cemented. A periodontal ligament was simulated using polyether. A force was applied to the palatine portion of each sample at 45°, until fracture. Fracture resistance data were submitted to two-way ANOVA and Tukey's test (α = 0.05). Three-dimensional digital models were developed to calculate the tensions formed in the root using finite element analysis. Models of glass fiber posts and PEEK posts and cores were evaluated with or without a ferrule. The results were analyzed by the Mohr-Coulomb criterion. The type of IR was not influenced by fracture strength (p = 0.243). There were significant statistical differences among the remaining factors. Ferrule groups had greater fracture resistance, and the failure mode of teeth with a ferrule was more catastrophic than the non-ferrule group. A ferrule increases fracture resistance and influences failure mode; the PEEK post and core did not modify the biomechanics of endodontically treated teeth, and resembled the glass fiber post results. The crack initiation point differed between the ferrule and non-ferrule groups.